The Era of Modernization: Digital Technology Marketing Strategies in Tourist Attraction Development - Nerisma Eka Putri; Muhammad Azkia Fahmi; Randu Rahmatan Hanif; Khaidir Ali Junid (Indonesian Tourism Journal, 2025)
The rapid advancement of digital technology has transformed how tourism destinations are promoted and managed, reshaping the competitiveness of ecotourism in the modern era. This study investigates digital technology–based marketing strategies for developing tourist attractions by integrating sustainability and community participation. The research aims to identify effective approaches for enhancing destination visibility and engagement through major social media platforms such as TikTok, Instagram, YouTube, and official tourism websites. Using a qualitative descriptive method, data were collected from literature reviews, online promotional content, and interviews with tourism stakeholders, including destination managers, digital marketing practitioners, and tourists. Analysis employed the Miles and Huberman model, encompassing data reduction, display, and conclusion drawing. The findings reveal that digital marketing significantly strengthens destination appeal through strategies tailored to each platform TikTok for virality, Instagram for branding, YouTube for in-depth storytelling, and websites for official information. Moreover, sustainable digitalization initiatives, including educational content, online booking systems, and collaborations with influencers and environmental NGOs, enhance conservation awareness and tourist experience. The study concludes that integrating digital marketing with sustainability principles fosters effective promotion and stakeholder synergy, while the government’s regulatory and facilitative roles are essential to ensuring alignment with eco-tourism values and long-term development goals.